2023
DOI: 10.1124/jpet.122.001493
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Monotherapy Alters the Human Plasma Lipidome Independent of Clinical Markers of Glycemic Control and Cardiovascular Disease Risk in a Type 2 Diabetes Clinical Cohort

Abstract: Type 2 diabetes (T2D) is a rising pandemic worldwide. Diet and lifestyle changes are typically the first intervention for T2D. When this intervention fails, the biguanide, metformin, is the most common pharmaceutical therapy. Yet, it's full mechanisms of action remain unknown. In this work, we applied an ultrahigh resolution, mass spectrometry-based platform for untargeted plasma metabolomics to human plasma samples from a case-control observational study of non-diabetic and well-controlled T2D subjects, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Studies have shown that hypoglycemic agents influence metabolomic and lipidomic profiles in humans . Among diabetic patients with good blood glucose control, the overall lipidomic status of patients taking metformin was closer to that of patients without diabetes when compared with diet and lifestyle interventions . Therefore, given that approximately 50% of PDR patients (24/49) in this study were using oral hypoglycemic agents, this difference in medication use may lead to the identification of fewer differential metabolites and lipids.…”
Section: Discussionmentioning
confidence: 82%
“…Studies have shown that hypoglycemic agents influence metabolomic and lipidomic profiles in humans . Among diabetic patients with good blood glucose control, the overall lipidomic status of patients taking metformin was closer to that of patients without diabetes when compared with diet and lifestyle interventions . Therefore, given that approximately 50% of PDR patients (24/49) in this study were using oral hypoglycemic agents, this difference in medication use may lead to the identification of fewer differential metabolites and lipids.…”
Section: Discussionmentioning
confidence: 82%
“…In the first article, type 2 diabetic patients treated with metformin showed reduced plasma levels of lipid metabolites known to associate with cardiovascular disease risk. Inasmuch as lipidome changes were independent of glycemic control and pre-existing cardiovascular risk, these results suggested that an old drug such as metformin might represent a new cardioprotective agent (Wancewicz et al, 2023). In the second "drug repurposing" article the venerable aspirin, unparalleled game changer in cardiovascular prevention, is reviewed for mechanisms and clinical evidence of preventive effects against colorectal cancer and other cancers of the digestive tract, something that could only be reconciled with the seemingly unlimited ramifications of aspirin-dependent inhibition of cyclooxygenases (Patrono, 2023).…”
mentioning
confidence: 91%
“…Second, it is essential to efficiently detect and identify the extracted metabolites. There are multiple mass spectrometry (MS)-based platforms that can be used for the analysis of metabolites, each having its own unique advantage. As previously demonstrated, direct infusion workflows can rapidly and reproducibly detect hundreds of metabolites when coupled with ultrahigh-resolution MS. , On the other hand, there are many pathways that contain isomeric metabolites (e.g., leucine and isoleucine) which require the implementation of additional separation strategies prior to MS detection. As a complementary technique, liquid chromatography (LC) separation coupled to high-resolution MS allows for the separation of some structural isomers while providing high-resolution detection. , Moreover, tandem mass spectra (MS/MS) can be generated by using this approach, allowing for fragmentation matching.…”
Section: Introductionmentioning
confidence: 99%